Systematic Literature Review Education and Training in the Context of Changes in the Labor Market Induced by the Digital Revolution: A Case Study of the Hospitality Sector - Mammadova, Bayaz (ADA University, 2023)
The digital revolution presents a vast array of development possibilities in differing industries. Higher education degrees in many fields, including hospitality, are challenged by changes in the labor market resulting from new technology and globalization (OECD, 2019). The notion of a graduate skills gap, dealing with the extent to which HEI’s prepare graduates for future employment, is often discussed in the literature (e.g., Chigbu & Nekhwevha, 2022). Graduates with specialized degrees in hospitality are struggling to find and maintain employment as technology leads to more jobs becoming automated, leading to the simultaneous de-skilling, and upskilling of the workforce (Brown, Lauder & Ashton, 2011; Oesch, 2013). Such industry changes create a mismatch between skills being taught to graduates during highly specialized degrees, and the new job market demands. It also raisesthe question of whether generalized degrees are more applicable (CIPD, 2015).
Keywords: Digital Revolution; Graduate Skills Gap; Automation in Hospitality